The Effect of Institutional Ownership and Capital Structure on Firm Value with Financial Distress as Moderated Variables in Non-Bank Companies Registered in IDX LQ45 2016 – 2018 - Sulistiyani, Tri; Rivai, Abdul; Suharto (International Journal of Social Sciences and English Literature, 2020)
This study aims to examine the effect of institutional, capital structure, firm value with financial distress as moderation. In this study, external secondary data is used, namely data obtained from the financial statements of non-bank companies listed on the LQ 45 Indonesia Stock Exchange 2016-2018. The sampling technique in this study was purposive sampling method. The analytical method used is path analysis. The results showed that institutional ownership has an effect on firm value. Even though the contribution is very small, it still contributes to changes in firm value The institutional ownership variable moderated by the financial distress variable shows that institutional ownership moderated by financial distress has no effect on firm value, meaning financial distress cannot moderate the effect of institutional ownership on firm value, meaning that if institutional ownership increases and increased financial distress will have an impact on the decline in stock performance so that the value of the company will decrease, and vice versa. Ownership variables in the company do not affect changes in firm value, this is possible because companies listed in LQ 45 are companies with good performance so that investors no longer see the proportion of ownership in the company but pay more. And finally, there is the influence of the capital structure variable on firm value which is moderated by financial distress, namely financial distress which is able to moderate the effect of capital structure on firm value. This means that if the capital structure rises and financial distress increases, the company value will increase.